Reliability Estimation Of N-Component Parallel System by Bayesian Approach Using Inverse Rayleigh Distribution - K. Sandhya Rani, M. Tirumala Devi, T. Sumathi Uma Maheswari (Mathematical Statistician and Engineering Applications, 2022)
In this paper reliability estimation subjected to common stress using inverse Rayleigh distribution if X1, X2,…,Xn are strengths of n- components under one stress is derived. The estimation is performed by using Bayesian estimation under Jeffery’s prior and exponential prior distribution. Numerical calculations are done by matlab.